HIV/AIDS Epidemic in Multiple and Concurrent Sexual Relationships in Muslim countries - Biglarbeigi, Amir; Salami, Ismail; Mozaheb, Mohammad Amin (Advances in Social Sciences Research Journal, 2014)
In Islamic countries, including Iran, Muslims are allowed to have multiple and concurrent sexual partners provided that they make their sexual relationships official as temporary or permanent marriages. The authors of this commentary contend that while the law being against human rights conventions, this can ease the detection of those involved in multiple and concurrent sexual relationships and give HIV activists an ample opportunity to intervene and raise the awareness of men and women having such relationships. To test this contention, the authors asked one of the official marriage/divorce offices based in Tehran to distribute pamphlets regarding HIV/AID testing among those who wished to register their sexual encounters within the boundaries of a temporary marriage. 80 per cent of participants in this study were encouraged to do an HIV test before having any sexual encounters in temporary marriage.